A Case Report on Diabetic Foot Gangrene - Murthy, Krishna; Murthy, Deepthi Anand (Homœopathic Links, 2017)
We report a case of diabetic foot gangrene that was treated with homeopathic therapy which avoided a need for amputation of the limb. From this case report, we would like to suggest that there are better options like homeopathic therapy for a patient with diabetic foot gangrene rather than considering them for the amputation.
Keywords: Diabetes mellitus; Gangrene; Arsenicum album; Medorrhinum; Lachesis